Alteration of arsenopyrite in soils under different vegetation covers - Mihaljevic, Martin; Ettler, Vojtech; Sebek, Ondrej; Drahota, Petr; Strnad, Ladislav; Procházka, Radek; Zeman, Josef; Sracek, Ondra (The Science of the total environment, 2010)
The weathering of arsenopyrite (FeAsS) has been monitored in soils using an in situ experimental approach. Arsenopyrite in nylon experimental bags was placed in individual horizons in soils in spruce (litter, horizons A, B, and C), beech (litter, horizons A, B, and C) and unforested (horizons A, B, and C) areas and left in contact with the soil for a period of 1 year. The individual areas on the ridge of the Krusné hory Mts., Czech Republic, had the same lithology, climatic and environmental conditions. Scorodite (FeAsO(4).2H(2)O) was identified as a principal secondary mineral of arsenic (As) formed directly on the surface of the arsenopyrite. Scorodite was formed in all the areas in all soil horizons. The amount of scorodite formed decreased in the series beech, spruce and unforested areas. In forested areas, there was a larger amount of scorodite on arsenopyrites exposed in organic horizons (litter, A horizon). The greater rate of arsenopyrite alteration in organic horizons in the beech stand compared to spruce stand is probably a result of faster mineralization of organic material with resulting production of nitrate and better seepage conditions of soil in this area. Speciation of As determined using the sequential extraction technique demonstrated that As was bonded in the soils primarily in the residual fractions prior to the experiment. The As content in the mobile fractions increased in the organic horizon in the forested areas after the experiments.
Keywords: kinetika; monitorování životního prostředí; Microscopy, Electron, Scanning; minerály; látky znečišťující půdu; sulfidy; stromy; Iron Compounds; mikroskopie elektronová rastrovací; arsenikové přípravky; Environmental Monitoring; X-Ray Diffraction; Sulfides; Trees; půda; Soil Pollutants; Soil; sloučeniny železa; Kinetics; Minerals; Weather; počasí; difrakce rentgenového záření; Arsenicals